The Effects of the Visual Feedback Short Foot Exercise on Foot Alignment in Adults with Flexible Flatfoot - Jeong, Da-Woon (International Journal of Psychosocial Rehabilitation, 2024)
Flexible flatfoot occurs when the medial longitudinal arch collapses when weight bearing and returns to a normal arch when weight is removed with forefoot abduction and hindfoot valgus. This can cause pathological problems in the alignment of the lower extremities and the entire body. Recently, the short foot exercise has drawn attention as an intervention for flexible flatfoot. The purpose of this study is to investigate the effects of the short foot exercise with and without visual feedback on foot alignment in adults with flexible flatfoot. The subjects were 24 adults with flexible flatfoot. They were randomly assigned to a visual feedback short foot exercise group and short foot exercise group. Each group performed the exercise five times a week for six weeks. Foot alignment was measured using the picture archiving and communication system, and four radiological measurements were taken from lateral and antero-posterior x-rays (calcaneal inclination angle, lateral talocalcaneal angle, antero-posterior talocalcaneal angle, and antero-posterior talometatarsal angle). In the visual feedback short foot exercise group, the calcaneal inclination angle, lateral talocalcaneal angle, antero-posterior talocalcaneal angle, and antero-posterior talometatarsal angle showed significant differences. The short-foot exercise group showed significant differences for the calcaneal inclination angle and the antero-posterior talometatarsal angle. However, there were no significant differences between the groups. These results suggest that the short foot exercise is an effective exercise for young adults with flexible flatfoot in terms of changing foot alignment. Additionally, exercise with visual feedback is more effective for complete alignment of view, including the hindfoot